1989
DOI: 10.1111/j.1432-1033.1989.tb15220.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions in microsomal cytochrome P‐450 isozyme LM2 and their effect on substrate binding

Abstract: The effects of protein ~ protein interactions and substrate binding on the structure of the active site of rabbit liver microsomal cytochrome P-450 LM2 have been analyzed by resonance Kaman spectroscopy of the monomeric and oligomeric protein in solution. Also Hz02-dependent catalytic activities of the two states have been compared.The two vinyl substituents of the heme exhibit different orientations, as indicated by the frequencies and intensities of their stretching vibrations. One group lies in the plane of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
5
19
0
Order By: Relevance
“…In particular, it may be noted that the R R bands in LM4-In1 broaden compared to LM4" (~cLS), indicating that the chromophore assumes a more relaxed conformation after exchange of the axial ligand. Similar observations have been made for the effect of aggregate formation on the heme conformation in LM2 which yields distinct differences in the RR spectra [28]. Upon Im binding, however, the RR spectra of the monomeric and oligomeric LM2 become indistinguishable.…”
Section: H M Q W O T C I N Irzternr F Ionssupporting
confidence: 77%
See 2 more Smart Citations
“…In particular, it may be noted that the R R bands in LM4-In1 broaden compared to LM4" (~cLS), indicating that the chromophore assumes a more relaxed conformation after exchange of the axial ligand. Similar observations have been made for the effect of aggregate formation on the heme conformation in LM2 which yields distinct differences in the RR spectra [28]. Upon Im binding, however, the RR spectra of the monomeric and oligomeric LM2 become indistinguishable.…”
Section: H M Q W O T C I N Irzternr F Ionssupporting
confidence: 77%
“…These modes reveal the most pronounced differences comparing the ScHS and 6cLS states of LM4" as well as L M 2 . In a separate study, we have shown that the vinyl groups in LM2' are structurally different as indicated by two separated stretching vibrations [28]. This is apparently not the case for the 6cLS form of LM4".…”
Section: H M Q W O T C I N Irzternr F Ionsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the integrative connections in microsomal monooxygenase go far beyond that and involve functional effects of physical interactions of multiple P450 molecules that result in oligomerization (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Besides evidence of homooligomerization of various P450 species (10,12,15,(17)(18)(19)(20)(21)(22)(23), there are also multiple indications of interactions between dis-similar P450s in membranes of proteoliposomes (13), microsomes (14), and living cells (16).…”
mentioning
confidence: 99%
“…The reaction mixture was centrifuged at 5,000 rpm and, after that, the p-aminophenol determination was carried out following existing literature [25,26]. A volume of 0.25 mL of sodium carbonate 20% (p/v) and 0.75 mL of phenol 2% (p/v) were added to 0.5 mL of the supernatant and incubated at 37 ºC for 30 min.…”
Section: Determination Of P450 Activitymentioning
confidence: 99%